Toward a transdisciplinary educational method Draft-visualization: a didactic methodology - Giampiero Finocchiaro (Educación y Humanismo, 2022)
The predominance of an epistemological paradigm that remains linked to the linear, cumulative, and reductionist form of science highlights the delay with which transdisciplinarity spreads in the educational world.